Análisis técnico y financiero de las opciones de aprovechamiento de ERNC en la provisión de ACS al hotel Howard Johnson en la ciudad de Loja. - Castillo Maldonado, Carlos Humberto (2014)
Is analyzed the technical and financial options of unconventional renewable energy ERNC for providing hot water ACS to Howard Johnson hotel of Loja city. It start with the identification of energy applicants processes, the baseline of present ACS supply to rooms, pool and laundry is established; is identified the potential ERNC efficiency options to meet the established demand; and, is described the technical and financial relevance of technological proposals submitted by local suppliers